Improving Mental Health during the COVID-19 Pandemic through Online Psychoeducation - Fathiyah, Kartika Nur; Widyastuti, Tria; Setiawati, Farida Agus; Romadhani, Rahmatika Kurnia; Ayriza, Yulia; Abdullah, Yahya; Lilmuallafah, Lu'lu Inayatul (Faculty of Psychology, Universitas Negeri Yogyakarta, 2020)
The COVID-19 pandemic alters many aspects of everyday life that we have grown accustomed to. The enactment of various new policies to curb the spread of the disease, i.e., social distancing, work and study from home, restrictions on large-scale activities and restriction in travelling, compel each one of us to adjust. Not to mention the fear of being infected with COVID-19. These conditions led to various psychological problems such as anxiety, low hope, and negative emotions. Efforts to improve people's mental health are urgently needed. One such step is to increase one's understanding of self-management in facing psychological problems due to COVID-19. This study aims to improve the community's mental health, namely the residents of Blotan hamlet during the COVID-19 pandemic through online self-management psychoeducation. To test the effectiveness of psychoeducation, this study used a one-group pre and post-test design. A total of 31 subjects participated in the activity in full. We can infer the effectivity through the anxiety score, hope, and positive emotions on the pre and post-test measurements. The results found that self-managed psychoeducation facing psychological problems during the pandemic significantly increased positive emotions (t = -2,753, df = 30, and p <.05). As for the measurement of anxiety and hope, there was no significant change due to the subject's anxiety score and hope were already in the medium category.